2015
DOI: 10.5551/jat.26260
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Serum Uric Acid Level on Subclinical Atherosclerosis in Middle-aged and Elderly Chinese

Abstract: Aim:The carotid intima-media thickness (CIMT) is now validated as a sensitive marker of atherosclerosis and is directly associated with an increased risk of cardiovascular disease. Considering that the independent association between the serum uric acid level and CIMT remains controversial due to the complex interrelationship with other known cardiovascular risk factors, further studies are needed. The aim of the present study is to explore the association between the serum uric acid level and CIMT in a genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 44 publications
(43 reference statements)
2
21
1
1
Order By: Relevance
“…The prognosis of PAD is determined by complicated coronary heart disease and stroke 35) . Therefore, the present findings agree with the findings of recent studies that high serum uric acid levels are associated with increased cardiovascular disease mortality in Japanese men and women 25) and with subclinical atherosclerosis evaluated based on IMT in Chinese men and women 26) . Moreover, a recent clinical study demonstrated that serum uric acid levels are associated with coronary lipid-rich plaques in Japanese men and women 27) .…”
Section: Discussionsupporting
confidence: 93%
“…The prognosis of PAD is determined by complicated coronary heart disease and stroke 35) . Therefore, the present findings agree with the findings of recent studies that high serum uric acid levels are associated with increased cardiovascular disease mortality in Japanese men and women 25) and with subclinical atherosclerosis evaluated based on IMT in Chinese men and women 26) . Moreover, a recent clinical study demonstrated that serum uric acid levels are associated with coronary lipid-rich plaques in Japanese men and women 27) .…”
Section: Discussionsupporting
confidence: 93%
“…The positive associations between serum UA levels and other surrogate markers of atherosclerosis have generally been validated in previous cross-sectional studies. [4446] However, the results were not fully consistent depending on the measurement method and subgroup categories. Chen et al [46] suggests that there is a close association between serum UA level and atherosclerotic lesions regardless of the underlying comorbid conditions.…”
Section: Discussionmentioning
confidence: 93%
“…[4446] However, the results were not fully consistent depending on the measurement method and subgroup categories. Chen et al [46] suggests that there is a close association between serum UA level and atherosclerotic lesions regardless of the underlying comorbid conditions. In contrast, several other studies have been more compatible with our results in that the relationship between serum UA level and atherosclerotic disease depends on underlying comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Although the precise mechanism of the nephrotoxicity of HU has not been fully elucidated, recent data showed a direct harmful effect of UA on endothelial cells 59) and smooth muscle cells 60) . In humans, it has been reported that serum uric acid level is independently associated with an elevated carotid intimamedia thickness 61) . Therefore, UA injures renal vessels, which are the major lesion of arterial/arteriolar nephrosclerosis.…”
Section: Discussionmentioning
confidence: 99%